2020
DOI: 10.1038/s41598-020-76715-w
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free synthesis of the hirudin variant 1 of the blood-sucking leech Hirudo medicinalis

Abstract: Synthesis and purification of peptide drugs for medical applications is a challenging task. The leech-derived factor hirudin is in clinical use as an alternative to heparin in anticoagulatory therapies. So far, recombinant hirudin is mainly produced in bacterial or yeast expression systems. We describe the successful development and application of an alternative protocol for the synthesis of active hirudin based on a cell-free protein synthesis approach. Three different cell lysates were compared, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Despite HLF1 has no antithrombotic activity in previous studies, Muller et al found that similar thrombin-inhibiting activity to hirudins could be observed in HLF1 after N-terminal modification. Additionally, analogous phenomena could be found in HLF3 and HLF4 through modifications within the N-termini in combination with an exchange of the central globular domain (Muller et al, 2020) . These results suggested that the N-and C-termini as well as the central globular domains are crucial for hirudin and HLFs to exert antithrombotic activity.…”
Section: Hirudin-like Factorsmentioning
confidence: 56%
See 1 more Smart Citation
“…Despite HLF1 has no antithrombotic activity in previous studies, Muller et al found that similar thrombin-inhibiting activity to hirudins could be observed in HLF1 after N-terminal modification. Additionally, analogous phenomena could be found in HLF3 and HLF4 through modifications within the N-termini in combination with an exchange of the central globular domain (Muller et al, 2020) . These results suggested that the N-and C-termini as well as the central globular domains are crucial for hirudin and HLFs to exert antithrombotic activity.…”
Section: Hirudin-like Factorsmentioning
confidence: 56%
“…In recent decades, the hosts for expressing rH are also increasing, which vary from Bacillus subtilis (Chen et al, 2011) to Lactococcus lactis (Lv et al, 2012). rH can be produced not only by bacterial or yeast expression systems, but also by a cell-free protein synthesis approach, which can express rH with higher antithrombin activity (Wustenhagen et al, 2020). Although these methods can increase the expression of recombinant hirudin, the thrombin inhibition constant is still lower than that of natural hirudin, mainly because it lacks the tyrosine residue sulfated at site 63 (Nowak and Schror, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hirudin is the most potent natural thrombin inhibitor known [ 16 ]. It was found that the 3-kD part of leech has some shortening of APTT and PT, suggesting that the 3-kD part may have some hemostatic effects, which is an interesting phenomenon, indicating that some hemostatic components may exist in leech.…”
Section: Resultsmentioning
confidence: 99%
“…32 Nevertheless, the mentioned approaches are quite complex and give a low yield of hirudin, so the scalability of these technologies for future industrial applications is questionable and should be investigated. 33 Alternatively, recombinant hirudin without tyrosine sulfation could be produced on a large scale in prokaryotic 34,35 and eukaryotic expression systems [36][37][38] as well as by a cell-free protein synthesis approach, 39 because of the absence of required sulfotransferases in these expression systems. However, recombinant desulfo-hirudin exhibits a 10-fold decrease in inhibitory potency compared to wildtype hirudin, 24,40 that makes sulfo-hirudin more advantageous to use in the clinic.…”
Section: Introductionmentioning
confidence: 99%